The Influence of Service Quality and Price on The Decision to Use Grab Services - Rauf, Nuzmerini; Darman; Hunowu, Abd. Hamid (Eastasouth Institute, 2023)
This research was conducted to determine the influence of service quality and price on the decision to use Grab services in Gorontalo. The sampling technique used was Accidental Sampling by determining 50 respondents. The research method uses quantitative descriptive with the Statistical Program for Social Science (SPSS). The results of this research show that Service Quality and Price significantly influence the Decision to Use Grab Services with an F value of 22.528, with a total influence of 0.484 or 48.4%. Service Quality has a significant effect on the Decision to Use Grab Services with a t-value of 4.021, Price has a significant effect on the Decision to Use Grab Services with a t-value of 3.415.